The proliferating cell nuclear antigen (PCNA) is a potential proliferative marker in oyster Crassostrea gigas. Issue 122 (March 2022) - Yu, Simiao; Qiao, Xue; Song, Xiaorui; Yang, Ying; Zhang, Dan; Sun, Wending; Wang, Lingling; Song, Linsheng
Abstract: Proliferating cell nuclear antigen (PCNA) is a crucial eukaryotic replication accessory factor in the regulation of DNA synthesis, which is always used as a proliferation marker for haematopoiesis in vertebrates. In the present study, a homologue of PCNA (named as Cg PCNA) with a conserved N -terminal PCNA domain and a C -terminal PCNA domain was identified from oyster Crassostrea gigas. The deduced amino acid sequence of Cg PCNA shared 85.4% and 86.6% similarities with the PCNAs identified in Mus musculus and Homo sapiens, respectively. Cg PCNA was firstly clustered with PCNAs from molluscs, and then with PCNAs from arthropods to form a group falling into the invertebrate clade in the phylogenic tree. The mRNA transcripts of Cg PCNA were detected in all tested tissues with higher expression level in gonad, gills and haemolymph. They were also detected in granulocytes, semi-granulocytes and agranulocytes with no significant differences, but the protein level of Cg PCNA in agranulocytes was significantly higher (3.67-fold, p < 0.05) than that in granulocytes. In the haemocytes, Cg PCNA was mainly distributed in the nucleus and less in the cytoplasm of haemocytes. Cg PCNA protein was observed at the tubule lumen regions of gills vessels, and especially colocalized with the EdU signals. After lipopolysaccharide (LPS) and Vibrio splendidus stimulation, the expression level of Cg PCNA mRNA in haemocytes was significantly ( p < 0.05) up-regulated at 6 h and 12 h, which was 13.87-fold and 3.89-fold of that in control, respectively. In the oysters treated with the recombinant protein Cg Astakine (r Cg Astakine), the protein abundance of Cg PCNA was enhanced in agranulocytes and gills, while no significant change was observed in semi-granulocytes and granulocytes. These results collectively indicated that Cg PCNA was highly expressed in the newborn agranulocytes and the potential haematopoietic sites, and it might be applied as a marker for haemocytes proliferation in oysters. Highlights: A homologue of proliferating cell nuclear antigen molecule (PCNA) was identified in Pacific oyster C. gigas. The expression level of Cg PCNA mRNA in haemocytes was significantly up-regulated post LPS and V. splendidus stimulation. Cg PCNA was highly expressed in the newborn cells agranulocytes and the potential haematopoietic sites. Cg PCNA might be applied as a marker for haemocytes proliferation in oysters.